2018
DOI: 10.22159/ajpcr.2018.v11i4.23739
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Tinocrisposide by Inhibiting Nitric Oxide Production in Lipopolysaccharides-Stimulated Raw 264.7 Cells

Abstract: Objective: The aim of this study was to investigate in vitro anti-inflammatory activity of tinocrisposide using lipopolysaccharides (LPS)-stimulated RAW 264.7 macrophage cells. Tinocrisposide is a furano diterpene glycoside that was isolated in our previous study from Tinospora crispa.Methods: Anti-inflammatory effect was quantified spectrometrically using Griess method by measuring nitric oxide (NO) production after the addition of Griess reagent.Results: The sample concentrations of 1, 5, 25, 50, and 100 μM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…f. & Thomson was by far the most commonly reported species for treatments of diabetes in traditional Thai medicine. Apart from its use in diabetes treatments, it has been used as an anti-inflammatory based on its tinocriposide content [65], as a cardioprotective to treat hypertension [48] as well as an immunomodulatory, cytotoxic, and antimalarial herbal drug [66]. Results from several studies have confirmed that T. crispa is effective for diabetes treatment [67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…f. & Thomson was by far the most commonly reported species for treatments of diabetes in traditional Thai medicine. Apart from its use in diabetes treatments, it has been used as an anti-inflammatory based on its tinocriposide content [65], as a cardioprotective to treat hypertension [48] as well as an immunomodulatory, cytotoxic, and antimalarial herbal drug [66]. Results from several studies have confirmed that T. crispa is effective for diabetes treatment [67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…It is due to the content of tinocrisposid compounds, flavonoids, such as quercetin, aporphine, berberine, and palmatine as antiinflammatory and antimalarial compounds. [13] It inhibits tubular damage caused by immune responses during malaria infection, either by host immune cells or parasites. According to Rathe et al, (2009), the compounds compound flavonoids inhibit the production of Nitric oxide (NO), Inducible Nitrite oxide (INOS) and NF-kβ activation in macrophage cells stimulated by lipopolysaccharides.…”
Section: Histopathological Changes In Tubulesmentioning
confidence: 99%
“…The result is due to antiparasitic and anti-inflammatory effects. [12,13,15,30,31,32] Changes in NF-kβ expression levels…”
Section: Histopathological Changes In Tubulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in our previous research, various concentrations of tinocrisposide were tested against the LPSstimulated RAW 264.7 cells, and the results showed the decrease of NO level production in concentration activity-dependent manner, with half-maximal inhibition concentration of 46.92 μM. Thus, it can be developed as anti-inflammatory candidate drug because NO is a reactive nitrogen species which is produced by NO synthase [10]. S. Chanda and A.R.…”
Section: Introductionmentioning
confidence: 97%